APPLICATION OF DIGITAL TECHNOLOGIES IN THE FIELD OF EDUCATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The article illustrates about digital technology, cloud technologies, use of digital technologies in education, tools of digital technology education system, advantages of digital technology, Internet of Things, augmented reality, virtual reality. Moreover, you can get information about these what digital technologies can be used in the educational process, and solutions to the problems encountered during their use.